Active Earth Pressure for Sloping Finite Soil While Accounting for Shear Stress and Curved Slip Surface. (15th September 2022) - Wang, Weiwei; Liu, Xinxi; Hu, Weidong; Luo, Hua; Wang, Guanghui
Abstract : Calculating the earth pressure of the sloping soil having finite width behind the retaining wall is difficult for stability calculation. Thus, a novel method to calculate the active pressure of cohesionless sloping finite soil behind a retaining wall was developed to investigate. Taking cohesionless soil as the research object and considering the principal stress rotation of soil, the resultant force for active earth pressure, action point position, and earth pressure distribution of sloping finite soil was obtained based on assumptions of the translational mode of the rigid retaining wall and cycloidal slip surface. The accuracy of the proposed method was verified by model tests. The influence of the slope height ratio l / H and slope angle α on earth pressure was analyzed in this study. The result revealed that the horizontal component of the active earth pressure distribution curve for sloping finite soil was linear in area I and nonlinear with a drum shape in area II. There was a noticeable change at the junction of the two areas. The resultant force of earth pressure and the height of action point of resultant force increased and tended to reach a certain value as the aspect ratio l / H increased. When l / H ≥ 0.4, the height of the action point of resultant force tended to be two-fifths the height of the wall. The resultant force and the height of the action point decreased linearly as the slope bottom angle increased.